FERMENTASI KULIT BUAH KAKAO (Theobroma cacao) SEBAGAI BAHAN PAKAN TERNAK - Syaiful Umela (UPPM Politeknik Gorontalo, 2016)
Waste pod husks potential to be used as fodder, particularly for the provision of ruminant feed. In the dry season grass growth is inhibited, so that the availability of forage less and the quality is low. That places forage shortage, given the availability of forage is limited, the strategic steps that can be taken is to utilize waste pod husks as animal feed. Animal feed is made by combining the rind cocoa fermented with corn bran and rice bran.This study aims to find ways of processing the cocoa fruit skin through fermentation and to determine the nutritional composition of animal feed produced pod husks. The method used in this study is a completely randomized design (CRD). Data obtained through organoleptic and proximate analysis.The results of organoleptic tests showed the best quality feed pod husks are treated P2 (fermented cocoa skin of 3000 g, 1000 g of corn bran and rice bran 2000 g) color with an average value of 3.80, the texture with an average value of 3.73 and proximate analysis results concentrate fermented cocoa skin is treated P2, the nutritional composition of the water content of 12.97%, ash content of 19.55%, 5.49% protein and 49.57% crude fiber.